TI_GERICHTE 60.2004.286 vom 7. Oktober 2004 , ricorso contro l'atto di accusa. appropriazione indebita (art. 138 CP e art. 140 vCP). - TI Tribunale d'appello (2004)
ricorso contro l'atto di accusa. appropriazione indebita (art. 138 CP e art. 140 vCP).